Tensile properties of ternary blends for HDPE/PP/Recycle HDPE in blow moulding process - Md Ali, Mohd Amran; Abdullah, Abu; Mohamad, Effendi; Salleh, Mohd Shukor; Hussein, Nur Izan Syahriah; Muhammad, Z.; Dahaman, Shamshulizam (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Increasing the environmental concern among peoples have increased the recycling activities, especially for high-density polyethylene (HDPE) bottles. Therefore, recycled HDPE needs to be mixed with other plastic materials to improve their mechanical properties. In this study, recycled HDPE was mixed with virgin HDPE and polypropylene (PP). The ratio of virgin HDPE and PP were set at 10/90, 30/70 and 50/50, meanwhile recycled HDPE was set at 20%, 35% and 50%. The blended materials were extruded into the parison and was blown using extruded blow-moulding machine to produce a 5-litre bottle. The tensile strength and elongation at break of the blended materials were measured using universal testing machine (UTM). Miscibility of the blended materials was also evaluated using differential scanning calorimetry (DSC). The result shows that decreasing the recycled HDPE in the blended materials increases the tensile strength. Meanwhile, increasing the recycled HDPE content in the blended materials increases the elongation at break of the blended materials. DSC curve shows that blended materials are immiscible.